MORPHOBIOLOGICAL CHARACTERISTICS OF THE MEDICINAL AMARANTH PLANT - Abdukhalilova Madinakhon (Journals Park Publishing, 2023)
The article contains information about the geobotanical description of the medicinal amaranth plant, the role of certain substances included in this plant in human health, and the characteristics of the plant's growth and development during the vegetative period.
Keywords: Extraction, concentration, squalene, protein, osteochondrosis, arthrosis.